CHARACTER BUILDING THROUGH THE APPLICATION OF SANTRI PLEDGE VALUES AT MA PERSIS 03 PAMEUNGPEUK GARUT - Cecep Nasrul Yakin; Ace Suryadi; Kama Abdul Hakam (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
The purpose of this research is to describe the stages of value internalization through the implementation of the Santri pledge at MA Persis 03 Pameungpeuk. The research method used is using a qualitative descriptive analysis. The results of the study revealed that the application of the Santri pledge became character-building. The character development of making promises/pledges is related to the value of trustworthiness and obedience in the sense that trustworthiness and obedience are not only applied to school institutions but in essence, carry out mandate and obedience to Allah SWT. The results obtained from the first point regarding the value of trust, when viewed from the stage of internalization of values have reached the stage of moral values, meaning that the internalization of trust values in MA Persis 03 Pameungpeuk does not only occur at the information stage but has reached the stage of belief, attitude to the stage of moral values. , while the character and dignity stages are yet to be seen.